TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERSEROAN TERBATAS - Pohan, Amrul Partomuan (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Through the development of Legal Theory that started fromthe period of Ancient Rome, when the legal concept ofCorporation was created and then admitted as “independent(separate) legal entity” that may conduct legal action similarto individual. The resemblance of Corporation with individualcontinued in Legal Theory with the concept of “CorporateCrime”, and further with the concept of “Good CorporateCitizen”, in which the Company is expected to also payattention to the interest of its surrounding community, and theenvironment (not only for its own interest).The Company Law uses the term TJSL instead of CSR toemphasize the important role of the Company in participatingin the environmental management. The Company Lawconsiders that the Company responsibility upon the naturalresources is fundamental. Therefore, the Company Lawprovides that the implementation of TJSL is compulsory forthe Company which manage or affect natural resources.The Company Law underlines the requirement for TJSL thathas been provided under certain prevailing laws, among others,laws on Industry, Environment, Prohibition on MonopolyPractices and Unfair Competition, Human Rights, Forestry,Employment, State Owned Company, Water Resources,Mineral Mining and Coal. The Company Law provides thatTJSL should be incorporated in the business plan and budget,and the budget should be determined by the Company withdue regard to the reasonableness and fairness. Theimplementation of which should be included in the AnnualReport.The Company which business activity does not manage noraffect to the natural resources may also implement the TJSL.Basically, the Company Law urges each Company tovoluntarily implement the TJSL, and for which the Companymay be awarded with an Award as appreciation from theauthority, provided further that the TJSL should be includedin the annual business plan and budget.